ISPC Commentary on the Proposal for CRP1.2 - October 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC commentary on the Proposal for CRP 1.2: Humid tropics.